2019
DOI: 10.1098/rspb.2019.1466
|View full text |Cite
|
Sign up to set email alerts
|

Differences in mitochondrial efficiency explain individual variation in growth performance

Abstract: The physiological causes of intraspecific differences in fitness components such as growth rate are currently a source of debate. It has been suggested that differences in energy metabolism may drive variation in growth, but it remains unclear whether covariation between growth rates and energy metabolism is: (i) a result of certain individuals acquiring and consequently allocating more resources to growth, and/or is (ii) determined by variation in the efficiency with which those resources are transformed into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 49 publications
3
63
0
Order By: Relevance
“…The thermodynamically mediated increase in ATP demand in response to warming is therefore exacerbated by reduced mitochondrial efficiency. Consequently, greater amounts of food‐derived substrates and oxygen are required to produce the same amount of ATP to meet this demand (Salin et al ., 2019).…”
Section: Metabolism Mitochondria and Musclementioning
confidence: 99%
See 2 more Smart Citations
“…The thermodynamically mediated increase in ATP demand in response to warming is therefore exacerbated by reduced mitochondrial efficiency. Consequently, greater amounts of food‐derived substrates and oxygen are required to produce the same amount of ATP to meet this demand (Salin et al ., 2019).…”
Section: Metabolism Mitochondria and Musclementioning
confidence: 99%
“…Oxygen supply and mitochondrial ATP production can influence growth rates. For example, increased mitochondrial inefficiency led to decreased growth rates in trout ( Salmo trutta , Linnaeus, 1758) (Salin et al ., 2019). Increased mitochondrial inefficiency means that less biomass is produced for a given amount of food eaten.…”
Section: Metabolism Mitochondria and Musclementioning
confidence: 99%
See 1 more Smart Citation
“…These mechanisms might either prevent damage in cells by reducing the generation of ROS, or repair the damage already caused. Both metabolic rate, usually measured in terms of whole‐body oxygen consumption, and mitochondrial efficiency, defined as the amount of ATP generated per molecule of oxygen consumed, show great within‐ and among‐individual variation, and can change in response to environmental conditions (Salin, Auer, Rey, Selman, & Metcalfe, 2015; Salin et al., 2019). Metabolic plasticity at the organelle and tissue/organ level may allow organisms to adjust ROS production to increase their resilience to climate change (Norin & Metcalfe, 2019; Seebacher et al., 2015).…”
Section: Candidate Mechanisms To Buffer the Effects Of Warming On Agementioning
confidence: 99%
“…For example, Salin et al . () recently showed that individual differences in the growth rate of brown trout ( Salmo trutta ) are correlated with the efficiency of ATP production by the liver. While recent studies have made great strides in understanding the relationship between energy production and whole‐animal performance, there is still considerable, unexplained variation in performance among individuals and species.…”
Section: Introductionmentioning
confidence: 99%